2018
DOI: 10.3389/fonc.2018.00339
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Plus Cetuximab as 1st Line Chemotherapy in Platinum-Based Chemoradiotherapy-Refractory Patients With Squamous Cell Carcinoma of the Head and Neck

Abstract: Purpose: We sought to evaluate the efficacy and safety of the combination of cetuximab (Cmab) and paclitaxel (PTX) in patients with squamous cell carcinoma of the head and neck (SCCHN) who had unresectable recurrent or metastatic (R/M) disease after platinum-based chemoradiotherapy.Materials and Methods: Data on 23 patients with SCCHN who received paclitaxel and cetuximab (Cmab) for R/M disease no more than 6 months after CRT completion were retrospectively reviewed. PTX and Cmab were given in a 28-day cycle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
7
17
6
Order By: Relevance
“…Despite the few existing data regarding the depth of responses with chemotherapy in SCCHN both in patients pretreated and non-pretreated with IO, responses to SCAI in our series showed a median PCTL of -57.5% (range: -30 to -100), which are deeper than the median PCTL of -40% reported by Enokida et al [31], in a Japanese series of 23 platinum-refractory patients receiving first-line ERBITAX -the most frequently used SCAI in our series. While only 30.4% of the patients in our series were platinum-refractory, all, per definition, were more pre-treated since they received SCAI as second or further line.…”
Section: Discussioncontrasting
confidence: 92%
“…Despite the few existing data regarding the depth of responses with chemotherapy in SCCHN both in patients pretreated and non-pretreated with IO, responses to SCAI in our series showed a median PCTL of -57.5% (range: -30 to -100), which are deeper than the median PCTL of -40% reported by Enokida et al [31], in a Japanese series of 23 platinum-refractory patients receiving first-line ERBITAX -the most frequently used SCAI in our series. While only 30.4% of the patients in our series were platinum-refractory, all, per definition, were more pre-treated since they received SCAI as second or further line.…”
Section: Discussioncontrasting
confidence: 92%
“…The Knoedler et al study evaluated cetuximab plus docetaxel in patients who failed a platinum-based therapy, achieving an overall disease control rate of 51% (85). Recently, a retrospective study showed that the combination of paclitaxel and cetuximab could be a suitable treatment option in HNSCC patients with platinum-based CRT-refractory disease (86).…”
Section: Recurrent or Metastatic Head And Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…Median PFS, OS, and response rates were significantly lower than in studies that have already studied this association. [8][9][10][11] However, in the publications of Enokida et al and Hitt et al, all patients were treated in a first-line setting and no patient had already been exposed to cetuximab, 8,9 which could explain the difference. In the two retrospective studies published by Péron and Fayette, patients could have been treated either in first or second line.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a 52%-54% response rate and 4.2-7.0 median PFS and 8.1-16.3 median OS. 8,9 In retrospective studies, PC showed high activity with a 48%-55% response rate, and a median OS of 7.6-9.2 months. However, in these retrospective studies, a significant proportion of patients were treated in a first-line setting because of their ineligibility for platinum chemotherapy.…”
Section: Introductionmentioning
confidence: 99%